2020
DOI: 10.7759/cureus.10848
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Social Support and Psychological Distress in Latina Mothers Living in Miami-Dade County, Florida

Abstract: Background: This study analysed the relationship between social support and psychological distress in Latina women in Miami-Dade County. Acculturation was examined as a modifying factor. Methods: A 2005 data set from interviews of 155 Latina mothers in Miami-Dade County, from motherdaughter dyads, was analysed. Social support was measured using the Interpersonal Support Evaluation List (ISEL) score. Psychological distress was based on self-reporting symptoms of depression, anxiety, or suicidality. Acculturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Immigration policy concerns and the perceptions of discrimination, social isolation, and family threats experienced by postpartum Hispanic mothers are unique stressors which may contribute to the mental health disparities observed during the COVID-19 pandemic. 19 , 23 , 48 Previous studies have found associations between perceptions of discrimination, social isolation, and familial threats and increased psychological distress and mental health issues among Latina mothers 13 , 49 but, this association has not been explored within the context of the COVID-19 pandemic or other natural disaster. However, a study by Mollard et al 17 explored the impacts of COVID-19 on stress and resilience factors, finding higher levels of stress and lower levels of resilience during the pandemic among postpartum women of color when compared to pre-pandemic norms.…”
Section: Discussionmentioning
confidence: 99%
“…Immigration policy concerns and the perceptions of discrimination, social isolation, and family threats experienced by postpartum Hispanic mothers are unique stressors which may contribute to the mental health disparities observed during the COVID-19 pandemic. 19 , 23 , 48 Previous studies have found associations between perceptions of discrimination, social isolation, and familial threats and increased psychological distress and mental health issues among Latina mothers 13 , 49 but, this association has not been explored within the context of the COVID-19 pandemic or other natural disaster. However, a study by Mollard et al 17 explored the impacts of COVID-19 on stress and resilience factors, finding higher levels of stress and lower levels of resilience during the pandemic among postpartum women of color when compared to pre-pandemic norms.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the process of acculturation where immigrants assimilate into the dominant culture [ 4 ]. The process of acculturation involves immigrants assimilating into the dominant culture, the process of acculturation also entails Qigong assimilating into the dominant culture.…”
Section: Introductionmentioning
confidence: 99%
“…The social support buffering hypothesis holds that social supports can mitigate the negative impact of stress on mental health ( 9 ). Lower levels of social support have been found to be associated with more mental health issues ( 10 , 11 ), and individuals with less social support are about five times more likely to experience symptoms of anxiety and depression than those that have greater social supports ( 12 ). People with low levels of social support are at a higher risk of psychological stress, while higher levels of social support can help to alleviate anxiety and depression ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%